2005
DOI: 10.1111/j.1742-4658.2005.04977.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of adrenal inner zone antigen as a heme‐binding protein

Abstract: The adrenal inner zone antigen (IZA), which reacts specifically with a monoclonal antibody raised against the fasciculata and reticularis zones of the rat adrenal, was previously found to be identical with a protein variously named 25‐Dx and membrane‐associated progesterone receptor. IZA was purified as a glutathione S‐transferase‐fused or His6‐fused protein, and its molecular properties were studied. The UV‐visible absorption and EPR spectra of the purified protein showed that IZA bound a heme chromophore in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(138 citation statements)
references
References 34 publications
(53 reference statements)
6
130
1
Order By: Relevance
“…There is additional evidence for regulation of rat PGRMC1 (also known as Vema, IZA, 25-Dx, and sometimes mPR) by progesterone and involvement of PGRMC1 in cellular, non-genomic progesterone responses (37)(38)(39)(40)(41)(42). However, progesterone binding by rat PGRMC1, was later shown to be nonspecific and weak by Min et al (5). Instead, they found that rat PGRMC1 bound heme and activated the cytochrome P 450 , CYP21, a key enzyme of progesterone biosynthesis, similar to the biological function proposed by Hughes et al (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is additional evidence for regulation of rat PGRMC1 (also known as Vema, IZA, 25-Dx, and sometimes mPR) by progesterone and involvement of PGRMC1 in cellular, non-genomic progesterone responses (37)(38)(39)(40)(41)(42). However, progesterone binding by rat PGRMC1, was later shown to be nonspecific and weak by Min et al (5). Instead, they found that rat PGRMC1 bound heme and activated the cytochrome P 450 , CYP21, a key enzyme of progesterone biosynthesis, similar to the biological function proposed by Hughes et al (8).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the ferrous heme does not bind well to Dap1p, the heme would likely dissociate during redox catalysis (35). Finally, attempts to reduce the rat Dap1p homologue, IZA, by P 450 reductases and cytochrome b 5 have been unsuccessful in vitro (9).…”
Section: Discussionmentioning
confidence: 99%
“…PGRMC1 is widespread in eukaryotes from yeast to human. Despite its name, it is controversial whether progesterone binds to PGRMC1 (Min et al, 2005;Peluso et al, 2008b), and its function has not been fully understood. PGRMC1 is expressed in many tissues including liver, kidney, brain, breast, and adrenals (Cahill, 2007;Lösel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In general, dimers can be separated under reducing condition. But the vertebrate PGRMC1 has been reported to form the homodimer even in reducing condition, suggesting the homodimer was linked covalently [9,18]. Dm_MSBP also may thus form a homodimer, and this dimerization may be involved in the function of Dm_MSBP at the beginning of metamorphosis.…”
Section: Cloning and Characterization Of Dm_msbp Cdnamentioning
confidence: 99%